Modularity and integration in the skull of canis lupus (Linnaeus 1758): a geometric morphometrics study on domestic dogs and wolves - Curth, Stefan (2018)
Domestic dogs stand out due to an enormous morphological variation of their skulls, which clearly surpasses the variation found in wolves. A frequent phenomenon among this variation is the occurrence of disproportions between skull modules which appear much more frequent and more pronounced in domestic dogs than in wolves. This phenomenon led up to the hypothesis that the integration of the skull modules in domestic dogs is degraded when compared to the wolf. Moreover, it was hypothesized that the patterns of covariation of skull modules were altered through artificial selection. In a first study, this hypothesis was tested using geometric morphometrics on 196 CT scanned dog and wolf skulls. The results point to an unchanged integration strength of the skull modules in domestic dogs. Also the covariation pattern of skull modules is very similar to that of wolves. Through this surprising result, the hypothesis for a second study was formed. The temporomandibular joint of dogs is highly diverse when compared to the joint of wolves. The reasons for this phenomenon have not been explored before. If the high integration in the domestic dog skull does also apply to the temporomandibular joint, the shape of the joint should be predictable on the basis of skull geometry. Also this hypothesis was tested using geometric morphometrics with a sample of 274 CT scanned skulls. The results showed that certain characteristics of the temporomandibular joint can be traced back to overall skull geometry (foremost relative muzzle length, skull flexion and size). Exceptions from this pattern are frequent though, and dogs with very similar skulls can have differently formed jaw joints. This points to a certain degree of structural independence of the jaw joint from the rest of the skull. The observed covariation patterns closely resemble patterns found in primates and humans, other carnivores and even pigeons, which suggests a highly conserved developmental program.